2017
DOI: 10.1371/journal.pone.0181928
|View full text |Cite
|
Sign up to set email alerts
|

Conformational risk factors of brachycephalic obstructive airway syndrome (BOAS) in pugs, French bulldogs, and bulldogs

Abstract: Extremely brachycephalic, or short-muzzled, dog breeds such as pugs, French bulldogs, and bulldogs are prone to the conformation-related respiratory disorder—brachycephalic obstructive airway syndrome (BOAS). Affected dogs present with a wide range of clinical signs from snoring and exercise intolerance, to life-threatening events such as syncope. In this study, conformational risk factors for BOAS that could potentially aid in breeding away from BOAS were sought. Six hundred and four pugs, French bulldogs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
140
5
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(161 citation statements)
references
References 38 publications
(40 reference statements)
4
140
5
12
Order By: Relevance
“…Although the large tongue of brachycephalic dogs is readily appreciable by oral examination, it has been noted uncommonly and inconsistently in the peer‐reviewed literature, and, when mentioned, it is typically unreferenced or cited as an earlier anecdotal observation . Possibly because of the lack of robust documentation, macroglossia is not listed as a feature of brachycephalism in many major veterinary texts, so awareness of it may be low in the veterinary profession .…”
Section: Introductionmentioning
confidence: 99%
“…Although the large tongue of brachycephalic dogs is readily appreciable by oral examination, it has been noted uncommonly and inconsistently in the peer‐reviewed literature, and, when mentioned, it is typically unreferenced or cited as an earlier anecdotal observation . Possibly because of the lack of robust documentation, macroglossia is not listed as a feature of brachycephalism in many major veterinary texts, so awareness of it may be low in the veterinary profession .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, age, body condition and laryngeal collapse have been identified as negative prognostic factors for surgical success (Torrez & Hunt , Liu et al . , , ), although these associations are not consistently found. Postsurgical complication rates of 12 to 26·2% and a mortality rate of approximately 3% have been reported (Poncet et al .…”
Section: Pre‐existing Conditions That Influence Anaesthetic Managementmentioning
confidence: 89%
“…In addition, there may be aberrant nasal turbinates, both rostrally and caudally, resulting in increased intranasal mucosal contact points and intranasal airway obstruction (Ginn et al 2008, Oechtering et al 2016. Studies have shown that brachycephaly predisposes to development of BOAS, with French bulldogs, pugs and English bulldogs being overrepresented (O'Neill et al 2015, Liu et al 2017b.…”
Section: Pre-existing Conditions That Influence Anaesthetic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…10 However, the most significant conformational factor in the three breeds is the degree of nostril stenosis (). Obesity is significant in pugs and the gender predisposition is interesting, with more male Frenchies and bulldogs being affected than females, and more female pugs being affected than males.…”
mentioning
confidence: 99%